QAIYARA CRUDE OIL RECOVERY IMPROVEMENT USING HOTWATER WITH SURFACTANT - Saeed, Essam (Iraqi Journal of Science, 2024)
The work is a method of an improving "Qaiyara" crude oil recovery using amixture of hot water with surfactant. Laboratory system was designed. Using thissystem, four tests of hot water with surfactant under various condition wereconducted. The first three tests are conducted under temperatures 50, 60, 80oCrespectively with mixture of hot water + 2% wt. surfactant. The fourth test is doneunder 80oC and mixture of hot water +4% surf. The result obtained show theefficiency of hot water with surfactant in improving the recovery. The results showproportioned relation between temperature and surfactant concentration with oilrecovery.